Removal of Chromium(VI) by Natural Polymer Chitin and Deacetylated Chitin from Aqueous Media. - N. VAISHNAV, SATISH; SHRIVASTAVA, V.S. (Asian Journal of Chemistry, 2010)
Chitin and its deacetylated form has been used as adsorbent for the removal of Cr(VI) in aqueous media. The effect of various parameters influencing the Cr(VI) adsorption such as pH, initial metal ion concentration and adsorbent dose has been studied. The optimum pH for adsorption of Cr(Vl) on chitin and deacetylated chitin was found to be 2.0 and 3.0 respectively. It has been found that metal removal percentage increases with adsorbent dose. Increase ininitial metal ion concentration decreases the percent removal but the amount of Cr(VI) adsorbed per unit weight of adsorbent increases. It has been also found thai deacetylated chitin shows greater potential for removal of Cr(VI) as compared to chitin. The data obtained from batch process was used to fit in Freundlich and Langmuir adsorption model.